The bachelor as young scholar: humanity-centric education process in an AI world - Rahman, Shukran Abdul (Mission Soft Foundation, 2025)
The world of higher education is standing at a challenging crossroads. With the rapid emergence of Artificial Intelligence (AI), the Internet of Things (IoT), and other forms of digital automation, the traditional method of learning is being reshaped faster than our institutions can adapt. As the mode of teaching and learning become increasingly sophisticated and accessible, we must ask several foundational questions, including what make student learning, what make undergraduate’ scholarship, and what make the human mind itself, in an era when machines can perform so much of what students were once trained to do? I am of the view that the existing framework of assessment in universities must undergo a judicious and principled shift, one which is grounded in awareness of the growing disruptions brought by artificial systems and one which is deeply rooted in principles and values (thawabit) that nurture humanity rather than dilute it.